2016
DOI: 10.1093/jxb/erw205
|View full text |Cite
|
Sign up to set email alerts
|

Regulation, overexpression, and target gene identification ofPotato Homeobox 15(POTH15) – a class-IKNOXgene in potato

Abstract: HighlightThis study demonstrates that overexpression of POTH15 (a class-I KNOX in potato) can alter multiple morphological traits, and identifies numerous POTH15 targets involved in diverse developmental processes in potato.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 90 publications
1
12
0
Order By: Relevance
“…2 C,D). In this study, authors further revealed that ~87% of randomly chosen POTH15 target genes had at least one tandem TGAC core motif in the 3.0 kb upstream sequence of the transcription start site, suggesting a possible BEL/KNOX interaction with the target genes (Mahajan et al, 2016). Many questions still remain to be answered regarding the functions of KNOX genes in potato.…”
Section: Mobile Rnas/proteins: Signals For Tuber Developmentmentioning
confidence: 74%
See 1 more Smart Citation
“…2 C,D). In this study, authors further revealed that ~87% of randomly chosen POTH15 target genes had at least one tandem TGAC core motif in the 3.0 kb upstream sequence of the transcription start site, suggesting a possible BEL/KNOX interaction with the target genes (Mahajan et al, 2016). Many questions still remain to be answered regarding the functions of KNOX genes in potato.…”
Section: Mobile Rnas/proteins: Signals For Tuber Developmentmentioning
confidence: 74%
“…KNOX genes also regulate levels of CK and auxin (reviewed in Hay and Tsiantis, 2010). Previous studies by Bolduc et al, (2012) and Mahajan et al, (2016) reported that KNOX-I genes target other homeobox TFs as well as hormone metabolism genes. Mahajan et al, (2016) showed that POTH15 over-expression affected diverse developmental processes in potato (e.g.…”
Section: Mobile Rnas/proteins: Signals For Tuber Developmentmentioning
confidence: 99%
“…The reads were aligned to the potato reference genome (PGSC_DM_v3.4_gene.fasta.zip) using the alignment software "STAR" (2.6.1c; Dobin et al, 2013). Downstream differential expression analysis of aligned reads was done using suite tools from "Tuxedo" (Trapnell et al, 2013), based on the protocol of Mahajan et al (2016). GO analysis was performed using the software "Blast2GO" v1.3.3 (https://www.blast2go.com/) for functional annotation of DE genes (Conesa et al, 2005;Götz et al, 2008), as described in Mahajan et al (2016).…”
Section: Rna-seq Analysismentioning
confidence: 99%
“…Downstream differential expression analysis of aligned reads was done using suite tools from "Tuxedo" (Trapnell et al, 2013), based on the protocol of Mahajan et al (2016). GO analysis was performed using the software "Blast2GO" v1.3.3 (https://www.blast2go.com/) for functional annotation of DE genes (Conesa et al, 2005;Götz et al, 2008), as described in Mahajan et al (2016). Validation of select target genes identified in the RNA-seq analysis was done using qPCR as described above in the "Tissue-Specific Transcript Abundance under SD and LD Conditions" section.…”
Section: Rna-seq Analysismentioning
confidence: 99%
“…In Populus , the type I KNOX gene PagKNAT2/6b has been demonstrated to directly suppress gibberellin biosynthesis, thereby promoting phenotypic alteration and enhancing plant drought stress tolerance ( Song X. et al, 2021 ). Similarly, POTH15, a type I KNOX gene, has been characterized as a regulator of photoperiodic development, meristem maintenance, and leaf development, and is believed to be involved in responses to plant hormone signal transduction and biotic or abiotic stresses, based on RNA sequencing and quantitative real-time PCR (qRT-PCR) validation ( Mahajan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%